MENINGKATKAN KEMAMPUAN SISWA MEMAHAMI ISI TEKS MELALUI IMPLEMENTASI MODEL PEMBELAJARAN PROBLEM BASED LEARNING - sukiasih, made (Journal of Education Action Research, 2018)
This research was conducted in Class IX-4 SMP Negeri 2 Singaraja in odd semester , year 2016/2017, with the average condition of the students ability in understanding the contents of the text only 71.11. This condition has not met the KKM. Percentage of new KKM achievement reached 29.73%. The purpose of this classroom action research is to improve students ability in understanding the text content through the implementation of Problem Based Learning Model Learning. The method used to collect data through the test description (the ability of students in understanding the contents of the text), which then analyzed by using descriptive method quantitative.The data are presented in the form of average learning achievement and learning mastery procession. The results obtained from this research is the development of students ability in understanding the text content was very positive. At first the average ability of students in understanding the content of the text only; 71,11 with complete learning only; 29.73%, then after the implementation of Cycle I increased to average, 75.35 with learning completeness reached 54.05% From Cycle I to Cycle II also increased the average that reached 79.19 and learning mastery 89.19 %. The conclusion obtained from this research is Implementation of Problem Based Learning Model can improve the ability of students of class IX-4 SMP Negeri 2 Singaraja in understanding the text content in odd semester at 2016/2017.